Representation of the Covid-19 Pandemic in Iranian Social Media - hadi khaniki; Ali Ahmadi (مطالعات رسانه‌های نوین, 2024)
Indeed, crises are an inherent part of society, and their number and diversity have increased significantly over time. Social media has emerged as a pivotal player in the prevention and management of crises, owing to its wide-reaching influence on audiences and its capacity to shape public opinion. The wide range of functions that social media provides makes it a significant pillar in managing crises. In this research, the most published content and the most visited posts of Telegram channels, related to the spread of coronavirus from March to September 2019, were analyzed to comprehensively represent the news on COVID-19 in Iranian social media. According to the research findings, as the frequency of content related to COVID-19 decreased, the significance of Telegram channel publications in the areas of quarantine, social distancing, and governmental measures for crisis management diminished as well. This led to a decrease in public sensitivity and attention towards the implementation of COVID-19 restrictions during the specified time frame. The decrease in public attention and sensitivity towards the application of COVID-19 restrictions is a significant factor that has contributed to the escalation of the crisis in society during the analyzed timeframe.  IntroductionThe COVID-19 pandemic has amplified the impact of social media on society, making it a more considerable and relevant news source compared to other mediums. Recognizing the critical function of the Telegram messenger in disseminating information, especially regarding the COVID-19 pandemic, analyzing the content shared through this platform offers valuable insights into changes in public sentiment within Iranian society during the crisis management phase.Research QuestionGiven Telegram's influence on shaping public opinion about COVID-19, how is the COVID-19 crisis represented in Iranian social media? Literature ReviewThe study conducted by Moradi and Mohammadifar (2019) entitled "The Role of Social Networks in Social Fear and Lifestyle Change Due to the Coronavirus" determined that Viber and Instagram had a more notable impact on increasing social anxiety in the city of Kermanshah, while domestic networks such as Ita and Soroush had a comparatively lesser influence on this aspect.Elahvardipour (2019) stressed the importance of health communication in countering COVID-19 misinformation worldwide. Zare (2019) underlines the swift spread of false information about COVID-19 and the necessity for structured management, while Bright et al. (2020) scrutinized state media coverage of COVID-19 in alignment with government policies. Sinelli et al. (2020) explored the role of social media in the spread of COVID-19-related misinformation and fake news. Sinelli et al. (2020) investigated COVID-19 rumors circulating on social media, and Harun and Rizvi (2020) examined its economic impacts. This study differentiates itself by delving into COVID-19 news on Telegram within Iranian society, a platform that holds significant potential for providing valuable insights into the shifting dynamics of public opinion.MethodologyThe research methodology employed in the current study is thematic analysis. In alignment with the primary focus of encapsulating the news related to the spread of the COVID-19 virus through the Telegram messenger, data analysis has been performed utilizing computer software with the assistance of the Data Mining Laboratory of the Faculty of Computer Engineering of the University of Tehran.In this research, a list of keywords relevant to the title of the research such as "corona, covid, coronavirus, virus, corona, mask" was prepared and the appropriate messages with these keywords were retrieved (Table 1). Ultimately, the 100 most visited Telegram messenger content from March 2018 to September 2019 were carefully chosen for analysis.ResultsDuring the analysis period spanning from March 2018 to September 2019, 15 themes related to the coronavirus pandemic on Telegram were examined:"Observing health principles" initially peaked in March 2018, but trended downwards consistently afterward, indicating decreasing interest among users."Quarantine and Adherence to Restrictions" saw elevated attention in the earlier stages, yet its significance diminished as time went on."Corona Disease Insurance" captured significant attention only during the initial stages of the outbreak, but this interest quickly dissipated soon after."Illnesses and Deaths due to Corona" witnessed the highest level of interest in June and September, which correlated with fluctuations in COVID-19 infection rates."Improving Corona" was at the forefront in March, showcasing initial efforts to manage the virus."Shortage of Healthcare Products" saw a notable surge in April but dwindled as the virus's magnitude lessened.- "Humor about Corona" emerged in August, signaling reduced public apprehension and a shift towards lighter discourse.During the designated period, "Actions by the government and the Ministry of Health" emerged as a significant aspect in May."Treatment Staff" received substantial notice in April but gradually lessened in significance later on."Experiences of Infection and Death of People Around You" reached a highest point of interest in April, mirroring increased public concern during periods of heightened mortality rates."Economic Effects of Corona" attained relatively limited attention, particularly in May, signifying a lower level of public awareness."Scientific material about the Coronavirus" witnessed increased attention over time, particularly during the second peak in July, indicating a growing comprehension of the virus."Muharram and coronavirus" became a significant topic of discussion in August and September, suggesting seasonal worries and concerns."Holding the entrance exam" as well as "reopening schools" in late summer 2019 were featured as pressing concerns, reflecting an emphasis on educational issues amidst the pandemic.ConclusionThe examination of Iranian social media channels between December 2019 and September 2020 unveiled several prominent themes related to the global pandemic of COVID-19. The main topics that garnered substantial attention encompassed quarantine measures, adherence to restrictions, disease incidence and fatalities, shortages of healthcare products, economic ramifications, and the observation of religious ceremonies, particularly Muharram.In general, themes associated with quarantine and government measures experienced a decrease in significance over time, suggesting a gradual decrease in Iranian sensitivity to restrictions during the pandemic. However, there was a notable change towards scientific information, notably concerning prevention and treatment measures for COVID-19, reflecting a growing interest in reliable information as the crisis evolved. The recurring focus on shortages of healthcare products, such as masks and alcohol, highlighted persistent concerns within the community. In contrast, personal experiences of infection and death experienced a decrease in attention, indicating a lesser level of public sensitivity towards COVID-19, possibly due to increased caution and awareness.AcknowledgmentsThis article has been developed from a research project undertaken by the Communication and Media Cluster at Allameh Tabataba'i University.